Michael Riffatere's Semiotics on Syiir Abu Tamam in the Book "Al Muwazanah Baina Syiir Abu Tamam Wa Al Buhturi" by Al Amidi (Alfaz (Arabic Literatures for Academic Zealots), 2022)
The material object in this study is the poem “Abu Tamam in the book Al Muwazanah Baina Syiir Abu Tamam Wa Al Buhturi”. The formal object of this research is Michael Riffatere's semiotic theory. The method in this research is descriptive qualitative. The results in this study through "heuristic reading, reading hermeneutics, matrices and hypograms on Abu Tamam's syiir entitled "Al-Dua li Al-Diyar Bi Al-Saqayaa Wa Al-Khosbu Wa Al-Nabaat", in the first stanza convey message about hope for rain. The second stanza describes the coming of spring after the rains that make the land fertile and then overgrown with shoots that will become fertile plants. The third stanza describes a deer playing with a deer. In the fourth stanza describes the condition of the rain that has passed and has entered another season.